Green Design; An Environmental Concern or an Aesthetic Approach - KARABETÇA, ALİYE RAHŞAN (My University, 2018)
The objective of this paper is to emphasize the importance and ethical concern of the green building design and its effects on climate change. It also aims to reveal the role of concerned designers in terms of conserving non-renewable resources and protecting environment in the field of architecture. Each designer (architects, interior architects, engineers, city planners, etc.) must find out what exactly an appropriate green design is. Apart from being an aesthetic approach, green design should be considered as an environmental concern. In his book Ecodesign, Ken Yeang explains that green design must follow the systematic rules of ecological design and it must also compete with other designs economically and must have outstanding quality in terms of user performance (Yeang, 2006).
Keywords: Green; Aesthetics; Environment; Certification; Biomimicry; Yeşil; Estetik; Çevre; Sertifikalandırma